2006
DOI: 10.1093/jmedent/43.4.647
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Phlebotomine Sand Flies on U.S. Military Operations at Tallil Air Base, Iraq: 1. Background, Military Situation, and Development of a "Leishmaniasis Control Program"

Abstract: One of the most signiÞcant modern day efforts to prevent and control an arthropodborne disease during a military deployment occurred when a team of U.S. military entomologists led efforts to characterize, prevent, and control leishmaniasis at Tallil Air Base (TAB), Iraq, during Operation Iraqi Freedom. Soon after arriving at TAB on 22 March 2003, military entomologists determined that 1) high numbers of sand ßies were present at TAB, 2) individual soldiers were receiving many sand ßy bites in a single night, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…The risk of cutaneous leishmaniasis for American military personnel early in the conflict prompted intensive vector control efforts. [39] Nine different insecticides, including organophosphates, pyrethroids and a carbamate, were used as residual sprays, space sprays and dustings for animal burrows. Despite the use of a wide spectrum of techniques and chemicals, the program appeared to have limited success in reducing sand fly populations.…”
Section: Role Of Vector Control In Prevention Of Leishmaniasismentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of cutaneous leishmaniasis for American military personnel early in the conflict prompted intensive vector control efforts. [39] Nine different insecticides, including organophosphates, pyrethroids and a carbamate, were used as residual sprays, space sprays and dustings for animal burrows. Despite the use of a wide spectrum of techniques and chemicals, the program appeared to have limited success in reducing sand fly populations.…”
Section: Role Of Vector Control In Prevention Of Leishmaniasismentioning
confidence: 99%
“…As mentioned earlier, these sprays had disappointing effects in the U.S. military cantonments of Iraq. [39] Likewise, DDT and malathion fogs in Sudan were not effective in reducing sand fly populations, the results being both small and short-lived. [44] Nevertheless, interior fogs are still a part of some programs and can provide temporary relief from insect bites.…”
Section: Role Of Vector Control In Prevention Of Leishmaniasismentioning
confidence: 99%
“…There is concern that asymptomatic latent leishmaniasis infection could be occurring in deployed troops that might cause subsequent disease in service members who later become immunosuppressed because of other diseases. Due to their small size and the fact that not enough is known about their biology, sand flies are difficult to control; to date, the use of air-conditioned quarters by service members in Iraq has proven to be the only effective countermeasure (Coleman et al 2006, Sanders et al 2005. Scrub typhus, a potentially life-threatening disease caused by Orientia tsutsugamushi bacteria that is transmitted to humans via bites from infected chiggers, has also impacted U.S. troops, particularly those engaged in jungle warfare in the Far East in World War II and the Vietnam War.…”
Section: Vector-transmitted Endemic Disease Threats To Deployed Us mentioning
confidence: 99%
“…A comparison of the SS-LP bed net with the Australian Defence Force (ADF) mosquito bed net found that both bed nets provided greater than 97.9% protection compared to unprotected personnel (Frances et al 2003), and the insecticide-untreated SS-LP bed net provided better night-time protection than the untreated ADF bed net. However, the small dimensions can provoke claustrophobia and the fine mesh of the SS-LP bed net limits air flow, which can cause overheating and noncompliance in hot climates (Coleman et al 2006).…”
Section: Bed Netsmentioning
confidence: 99%
“…No cases of L. major were reported, though the vector (P. papatasi) is a nuisance pest in the area (Schnur et al 2004, Orshan et al 2010. Conventional methods for outdoor sand fly control (e.g., residual and ULV spraying) are not only expensive and harmful to the environment, but they have also been proven ineffective in harsh desert conditions (Coleman et al 2006, Orshan et al 2006). The inconvenience posed by the nightly use of topical repellents has facilitated the search for alternative vector control methods that protect people against sand fly bites.…”
Section: Introductionmentioning
confidence: 99%